Pengembangan Permainan Tradisional Tabak Galang Berbasis Kearifan Lokal Gombang Pada Siswa Kelas V Sekolah Dasar - Dwi Sela; Erwin Putera Permana; Dhian Dwi Nur Wenda (STKIP PGRI SITUBONDO, 2022)
This research is a development research by designing the traditional game of Tabak Galang based on the local wisdom of Gombang. This study aims to determine the feasibility of the traditional game of Tabak Galang based on the local wisdom of Gombang for fifth grade elementary school students. The development procedure used in this study was adapted from the ADDIE development model which has five stages, namely analysis, design, design, implementation, and evaluation. Design and development includes limited testing and extensive testing to determine product feasibility. The results of this study were declared valid by the validator with a value of 91.6%, and the material received a value of 85.6%. The results of the limited trial were declared practical after obtaining the average overall result through a student response questionnaire with a score of 100% which showed more than 61% of students gave a positive response. And it is declared effective if 85% of students get a KKM score of 75, where eight fifth grade students get a score of 100% and have reached the criteria for completeness with an average value of 90. While the broad trial is declared practical after obtaining the average overall result through a teacher response questionnaire. which obtained 96% results and a student response questionnaire with a value of 95.5% which showed more than 61% of students gave a positive response. And it will be declared effective if 85% of students get a KKM value of 75 where 20 students of class V Mojoroto 4 Kediri, i.e. 95% have reached the criteria of completeness with an average value of 88. So the traditional game of Tabak Galang is suitable for use in learning, as well as the game of Tabak Galang This has advantages in improving students' critical thinking skills, collaboration in groups, group communication and a more pleasant classroom atmosphere.